The Difference Between Post-Laparoscopic Cystectomy Anti-Mullerian Hormone Levels In Endometrioma And Non-Endometrioma Cysts Patients - Kurniawan, Cornelius Danu (Faculty of Medicine, Diponegoro University, 2023)
Background: Endometrioma is a complex gynecological disease with increasing global prevalence. Laparoscopic cystectomy remains to be the primary choice of modality. Several studies, however, have revealed that laparoscopic cystectomy in endometriomas can cause ovarian damage and reduction in ovarian reserve. They demonstrated a decrease in serum AMH levels in endometrioma patients following laparoscopic cystectomyObjective: To identify the difference between the mean post-laparoscopic cystectomy AMH levels in endometrioma and non-endometrioma cysts patientsMethods: A prospective cohort study with 40 selected patients undergoing laparoscopic cystectomy in Kariadi General Hospital Semarang. They were divided into 2 groups of endometrioma and non-endometrioma cysts. AMH levels were measured before and after laparoscopic cystectomy surgery in both groupsResults: The mean age of endometrioma and non-endometrioma group were 32.40 ± 6.26 and 30.6 ± 3.69 years consecutively. The most common cysts were unilateral cysts with a diameter of > 4 cm which were dominated by endometrioma cysts. The group of subjects with endometrial cysts had lower AMH levels, both before (9.47 + 5.26 ng/mL) and after laparoscopic cystectomy (7.80 + 4.27 ng/mL). AMH levels before and after laparoscopic cystectomy in the endometrioma group showed a significant difference (p=0.004). In contrast, there was no significant difference in delta AMH between the non-endometrioma group (-1.63 + 4.12; p=0.685) and the endometrioma group (-1.74 + 2.37 ng/mL; p=0.685)Conclusion: Both endometrioma and non-endometrioma groups showed a decrease in AMH levels after laparoscopic cystectomy but they did not show a significant difference.